Lesões autoprovocadas intencionalmente em adolescentes residentes em Mato Grosso no período de 2011 a 2020 - Campos, Leonardo José Araujo de (2022)
Introduction. The group of self-inflicted injuries, which includes injuries with suicidal intent and without intent, is an important predictor of suicide. It is, therefore, a problem of social and public health relevance, given that suicide was, in 2019, the fourth leading cause of death in young people in the world .Objective. Analyze the reported cases of self-harm among adolescents residing in Mato Grosso, between 2011 and 2020. Methodology. Research with a quantitative approach, with an analytical descriptive design based on secondary databases. We studied the reported cases of self-harm in adolescents residing in Mato Grosso registered in the Violence and Accident Surveillance System of the Notifiable Diseases Information System between 2011 and 2020.The variables were selected from the Interpersonal and self-inflicted violence notification form. The degree of completeness agreed by ROMERO and CUNHA (2007) was measured and simple linear regression was used to investigate the trend of completeness of the variables. Notifications were described according to absolute and relative measures. Pearson's chi-square test was performed to compare the sexes and calculate the average annual notification rate in the health regions. Multiple correspondence analysis was used to identify patterns of association between sociodemographic characteristics and the occurrence of intentional self-harm. Results. There were 1,421 reports of self-harm in adolescents (10 to 19 years old). The completeness analysis included 40 fields, with 19 variables (47.5%) presented with “excellent” filling, eight (20.0%) with “good” filling, eight (20.0%) “regular” and five ( 12.5%) with “bad” filling. The completeness showed, mainly, a stationary trend. The female sex prevailed (75.0%), age group from 15 to 19 years old (75.4%), brown color/race (56.1%), occurred at home (88.8%), poisoning (50, 5%) as the medium used. Significant differences between the sexes were observed, except for the variables used, used at other times and presence of deficiency. Regarding the means of self-harm, 51.6% used poisoning, 28.4% used a sharp object and 9.8% used hanging. Statistical associations were found between the characteristics of adolescents and the main means of self-injury used; Correspondence analysis made it possible to identify three profiles of adolescents who performed self-harm. Conclusions. The results of this study reinforce the need to overcome barriers and taboos on the subject, enhancing health services for the reception, registration, surveillance and effective intervention of cases of self-harm. We suggest the inclusion of a variable capable of identifying whether the self-harm was with or without suicidal intent. We highlight the need for further investigation regarding the profiles of adolescents found in the study, expanding the knowledge bases on this emerging phenomenon, considering the specificities of the various subjects who carry out self-harm injuries and disseminating information on the subject to professionals and managers who work directly with them. the adolescent public, society and adolescents themselves.